Association of thyroid autoimmunity with extra-thyroid diseases and the risk of mortality among adults: evidence from the NHANES - Song, Jun-Long; Hu, Jia-Wei; Li, Ling-Rui; Xu, Zhi-Liang; Li, Juan-Juan; Sun, Sheng-Rong; Chen, Chuang (Frontiers in Endocrinology, 2024)
Background Thyroid autoimmunity is one of the most prevalent autoimmune diseases. However, its association with extra-thyroid diseases and mortality risk in the general population remains uncertain. Our study aims to evaluate the association of thyroid autoimmunity with extra-thyroid disease and the risk of mortality. Methods A prospective cohort study was conducted using data from the National Health and Nutrition Examination Survey (NHANES) with participants from 2007–2008, 2009–2010, and 2011–2012, tracking their mortality until 2019. Associations between thyroid autoimmunity, which was defined as having positive thyroid peroxidase antibody (TPOAb) and/or thyroglobulin antibody (TgAb), and extra-thyroid disease including diabetes, hypertension, cardiovascular disease, chronic lung disease, arthritis, cancer and chronic renal disease and the risk of mortality were investigated. Results A total of 7431 participants were included in this study. Positive The prevalence of positive TgAb was 7.54%, and positive TPOAb prevalence was 11.48%. TgAb was significantly associated with diabetes (Model 1: OR=1.64, 95% CI:1.08-2.50; Model 2: OR=1.93, 95% CI: 1.21-3.08) and hypertension (Model 1: OR=0.67, 95% CI: 0.49-0.91; Model 2: OR=0.62, 95% CI: 0.44-0.88). TPOAb was associated with a lower prevalence of chronic lung disease (model 1: OR=0.71, 95% CI: 0.54-0.95; model 2: OR=0.71, 95% CI: 0.53-0.95). No associations were observed between TgAb, TPOAb and other extra-thyroid diseases. Neither TgAb nor TPOAb were associated with all-cause mortality or heart disease mortality. Conclusion TgAb was linked to a higher prevalence of diabetes and a lower prevalence of hypertension, while TPOAb was associated with a decreased prevalence of chronic lung disease. However, neither TgAb nor TPOAb posed a risk for all-cause mortality or heart disease mortality.